2020
DOI: 10.1371/journal.pone.0242537
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of SARS-CoV-2 and clinical, epidemiological characteristics of COVID-19 patients in Hanoi, Vietnam

Abstract: A second cluster of COVID-19 cases imported from Europe occured in Vietnam from early March 2020. We describe 44 SARS-CoV-2 RT-PCR positive patients (cycle threshold value <30) admitted to the National Hospital for Tropical Diseases in Hanoi between March 6 and April 15 2020. Whole SARS-CoV-2 genomes from these patients were sequenced using Illumina Miseq and analysed for common genetic variants and relationships to local and globally circulating strains. Results showed that 32 cases were Vietnamese with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…A recent study showed that the SARS-CoV-2 with the G614 variant revealed increased infectivity, competitive fitness, and transmission than the wild-type D614 virus in human airway epithelial cells and hamster ( Hou et al, 2020 ). However, this mutation was not associated with the severity of COVID-19 ( Korber et al, 2020 ; Nguyen et al, 2020 ). Here, we aimed: (1) to report full-length genome sequences of SARS-CoV-2 collected from four COVID-19 patients in the Special Region of Yogyakarta and Central Java provinces, Indonesia; (2) to compare the clade distribution of full-length genome sequences from Indonesia ( n = 60) from March to September 2020; and (3) to perform phylogenetic analysis of SARS-CoV-2 complete genomes from different countries, including Indonesia.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study showed that the SARS-CoV-2 with the G614 variant revealed increased infectivity, competitive fitness, and transmission than the wild-type D614 virus in human airway epithelial cells and hamster ( Hou et al, 2020 ). However, this mutation was not associated with the severity of COVID-19 ( Korber et al, 2020 ; Nguyen et al, 2020 ). Here, we aimed: (1) to report full-length genome sequences of SARS-CoV-2 collected from four COVID-19 patients in the Special Region of Yogyakarta and Central Java provinces, Indonesia; (2) to compare the clade distribution of full-length genome sequences from Indonesia ( n = 60) from March to September 2020; and (3) to perform phylogenetic analysis of SARS-CoV-2 complete genomes from different countries, including Indonesia.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, SARS-CoV-2 with the D614G mutation became the most frequently detected globally, including South East Asia region ( Korber et al, 2020 ; Nguyen et al, 2020 ). Interestingly, SARS-CoV-2 with the G614 variant had significantly higher infectious titers than the original D614 virus, and COVID-19 patients with the G614 variant had a higher viral load than patients without the mutation ( Korber et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the combination of Spike D614G and NSP12 P323L in all detected SARS-CoV-2 variants indicates the importance of these two mutations in terms of transmission and pathogenicity rate (Hartley et al 2020 ; Kannan et al 2020 ; Mutlu et al 2020 ). A study from Vietnam cases, which also found D614G and P323L as the most common mutations, suggests that there is a high probability of the European origin of viruses in their samples as these two mutations are highly dominant in European samples (Nguyen et al 2020 ). Unlike the previous two mutations, only a few studies discuss the N3 Q57H mutation (Wang et al 2020 ; Soratto et al 2020 ; Hassan et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the SARS-CoV-2 with the G614 variant revealed increased infectivity, competitive fitness, and transmission than the wild-type D614 virus in human airway epithelial cells and hamster [7]. However, this mutation was not associated with the severity of COVID-19 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SARS-CoV-2 with the D614G mutation became the most frequently detected globally, including South East Asia region [5,6]. Interestingly, SARS-CoV-2 with the G614 variant had significantly higher infectious titers than the original D614 virus, and COVID-19 patients with the G614 variant had a higher viral load than patients without the mutation [5].…”
Section: Introductionmentioning
confidence: 99%